Improving Students' Motivation in Writing Procedure Texts Through MemoryRelated Strategy - Sri Wigatiningsih (Universitas Pancasakti Tegal, 2016)
This study was to investigate the memory related strategy in relation to students' motivation in writing procedure texts. The problems statement were formulated as follows: (1) what problems were faced by the students?; (2) how was Memory-related Strategy be implemented by the students?; (3) how could Memory-related strategy improve students' motivation in writing procedure texts? The design of the research was a Classroom Action Research. The subjects of this study were the seventh grader of SMP Negeri of 1 Larangan which consists of 38 students. This study was implemented in three cycles. The instruments used to collect the data were observation sheet, questionnaire, and students' product. The collected data were analyzed qualitatively. The score of students' writing improved from pre cycle to cycle 1 to cycle 2. It can be concluded that the use of memory related strategy was able to make the students enjoy the writing activities.